MANAJEMEN PENGELOLAAN OBJEK WISATA BERBASIS TEKNOLOGI INFORMASI DI KABUPATEN JEMBRANA - Jimmy Harry Putu Suarthana; Ida Bagus Kade Dwi Suta Negara (Badung: LPPM Universitas Triatma Mulya, 2019)
Tourism is one of the dominant income sectors for the island of Bali. Bali Island with a variety of tourist destinations spread across several regions, one of them is in Jembrana Regency. The lack of complete information makes several tourist destinations in Jembrana Regency not yet well known. By utilizing information technology, tourism managers can provide complete information to tourists and the public. The existence of this tourism object management system is expected to be one of the solutions in developing and promoting tourist destinations in Jembrana Regency so that it is better known and attracts the attention of tourists to visit. There are several facilities or features in this system including: data management, management of tourist objects, management of facilities, management of tourism events, and management of tourism promos. The results of user evaluations show that overall this system is good, but with this system some users expect that there will be additional features in this system.